Analisis Pengaruh Pertumbuhan Pendapatan Asli Daerah dan Pertumbuhan Belanja Modal Terhadap Fiscal Stress - Wilsna Rupilu; Eugenia Hendrini P. Tanan; Marthini Lakusa (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
This study aims to find out how the growth of PAD and capital expenditure of the regional government on the mainland of TimorIsland are affected by budget pressure (fiscal stress). Quantitative research methods and statistical analysis were used in this study. The data used is secondary data in the form of document data as the main means of data collection. Some common methods used to analyze data are linear regression analysis, hypothesis testing, and the use of classical assumptions. The results showed that the growth of PAD PEMDA mainland island of Timor had a positive effect on fiscal stress, besides that the results also showed that capital expenditure had a negatif effect on fiscal stress and simultaneously or simultaneously PAD and capital expenditure had an effect on fiscal stress.